The study of Effective and Efficient Organizational Change Processes with an Emphasis on Islamic Management - Fazel Hajizadeh Ebrahimi; Hamid Moakedi (پژوهش‌های مدیریت عمومی)
AbstractToday, effective and efficient change management has attracted the attention of managers in various organizations and companies from the highest management level to the last levels. In performing the current business, all managers should take into account the fact that making appropriate and effective changes has become one of the fixed features in the administrative system of the society. We are living in an era where changes are accelerated and we see fundamental and major changes around us every day. Organizations and people working in them should have a positive attitude towards the issue of change in order to maintain their competitiveness in today's aggressive markets. Ignoring a changing trend can be very costly. The Supreme Leader's emphasis on the importance of change and transformation in the administrative and governance sectors of the country and the lack of trust in Western versions is also a sign that this issue should be studied and investigated by relying on Islamic management at the organizational level. In this article, using a meta-analysis approach, studies published between 2001 and 2023 in the field of organizational change and Islamic management are selected as the statistical population. This article deals with the necessity of change in the management process of organizations in the society and offers suggestions regarding the effectiveness of organizational changes with emphasis on Islamic management.IntroductionIn some cases, organizations must constantly change and adapt to the external environment in order to survive. Management of organizational change and growth is one of the most important issues that managers of any organization should pay attention to it. Therefore, the analysis of effective and efficient change processes is necessary for growth in any organization that is studied in this article.Materials and MethodsThe purpose of this research is to analyze organizational change processes with emphasis on Islamic management. The research method used is qualitative methodology. Therefore, by applying the meta-analysis approach, the research conducted in the literature of this field was collected. In order to collect the studies, relevant keywords were used and the best researches were selected by searching the websites, books and specialized scientific journals.The questions of this research are:What are effective and efficient organizational change processes with emphasis on Islamic management?In this field, what are the differences between Islamic management and Western management?Discussion and ResultsOrganizations emphasize that management based on goals and especially management based on instructions are concepts of the past. Therefore, this type of management is no longer suitable for achieving competitive advantage in today's new business environment. Islamic management manages an organization based on values.From the point of view of Islamic management, the goals of the value-oriented organization can be presented as follows: 1. Perfecting the human being, 2. Promoting human dignity, and 3. Responding to the material and spiritual needs of the human being.Three types of organizational values, taking into account their desire for organizational changes, can be mentioned as follows: defensive values, stabilization values, and growth values.ConclusionWestern management is a set of methods and techniques to achieve the set goals of the organization. Therefore, the manager's art is in using all the abilities of the organization's employees and how to increase these abilities. Islamic management has been placed in a higher position than western management, which, in addition to western management methods and techniques, also pays attention to the aspects of how to achieve the goal and excellence of the organization's employees. As a result, the manager tries to achieve the goal within the framework of divine and Islamic values. Therefore, in Islamic management, it is effective and efficient to make changes that include moral and value issues (such as honesty and truthfulness, commitment, loyalty, humility, social justice, etc.), so that in addition to achieving the organizational goal, it also provides the means for the excellence of the organization and the spiritual growth of employees. Therefore, suggestions for effective and efficient organizational change are presented as follows:Familiarize employees with the planned changes and explain the advantages of new methods and new organizational values to them. Employees should know that the new changes will also benefit them. In this case, participatory change can be implemented in the organization.Solving organizational issues by making maximum use of existing organizations and facilities (understanding the value of flexibility in the organization).Rushing to change has a negative effect. Managers should allow the transformation in the organization to be implemented gradually (the principle of absorption in the change process).Managers should have direct contact with each person as much as possible. Managers can evaluate the quality of communication with employees of the organization by receiving feedback (understanding the value of communication between the leader and people).The feeling of need for change should be aroused in the existence of each and every person of the organization. For this purpose, methods such as audio-visual training or holding individual or group meetings can be used (principle of the need for change).The manager should talk to the critics and potential opponents of the change and attract their positive opinion by applying incentive policies (understanding the value of negotiating with the critics).Managers should involve the employees who resist the change in the change plan and give them spiritual and emotional support so that they stop resisting the change (understanding the value of participation and respect).Since changing is a voluntary and conscious process, in order to speed up its implementation, one should trust subordinates and give them authority (understanding the value of trust).The change program must have a divine intention and motivation so that it can be implemented and promoted by the spiritual support of God Almighty.Organizational change and transformation program will not succeed without a monitoring system. The program of transformation is monitored not only by the approved laws and requirements, but more importantly by the awakened human conscience, taking into account moral and value issues.One should note that according to values-based management, the types of organizational values are: defensive values, stabilization values, and growth values. Balanced businesses must operate on all three sets of values. Organizations with predominantly defensive values should also have at least some developmental values, and similarly, there will be some defensive values in organizations with dominant developmental values. Therefore, finding the optimal ratio of these three types of values is an important task for any organization in order to achieve effective and efficient change, and it depends on several factors such as the type of business, the type of management and culture, and the environment in which an organization operates.